Indian perspectives on China - Rajan, D. S. (Chennai Centre for China Studies KW Publisher Pvt. Ltd., 2013)
What are the implications of a rapidly rising China for India, and the rest of the world? How will the Sino-Indian relations unfold in the future? What are India's options? These questions were addressed in our first volume published in 2010 by writers who included former senior civil servants, academicians, and military experts. Continuing the effort are writers to the second volume, and we are sure that their findings will be useful to the policy planners as well as the research scholars both in the country and abroad. The scholars of the Chennai Centre for China Studies (C3S), a non-profit public policy think tank in Chennai devoted exclusively to China Studies, focus on analysis of contemporary economic, political, strategic, and international issues relating to China. Its website www.c3sindia.org provides a forum for specialists in India and abroad to closely examine the relevant issues.